UJI AKTIVITAS ANTIBAKTERI RIMPANG KUNYIT PUTIH (Kaempferia rotundaL.) TERHADAP Streptococcus sobrinus DAN Salmonella typhi - -, Nurfadzillah; Marliana, Eva; Ruga, Ritbey (JURNAL ATOMIK, 2021)
An infectious disease caused by bacteria is a disease that often occurs in tropical areas. The used of plant extract is an interesting object of study to overcome these infectious diseases and because of an increase in bacterial resistance to antibiotics. White turmeric rhizome widely used by Indonesia society as an herb which has been used for the treatment of diarrhea and abdominal pain. This study aims to determine the content of secondary metabolities and inhibitory of white turmeric rhizome (Kaempferia rotunda L.) against Streptococcus sobrinus KCCM 11898 and Salmonella typhi ATCC 422 bacteria. The results of phytochemical screening white turmeric rhizome contained compound triterpenoids, steroids, phenolics, and saponins. An antibacterial activity test used agar diffusion method against Streptococcus sobrinus KCCM 11898 and Salmonella typhi ATCC 422 bacteria. Antibacterial activity white turmeric rhizome (Kaempferia rotunda L.) with concentration 1, 2, 4, 8% have an inhibition zone diameter against Streptococcus sobrinus KCCM 11898 bacteria is 10.33, 10.67, 17 and 25.17 mm respectively with the antibacterial strength is strong, meanwhile in Salmonella typhi ATCC 422 bacteria have an inhibition zone diameter was 8, 8.3, 11.83 and 13 mm respectively with the antibacterial strength is intermediate. Keywords: Antibacterial, White Turmeric Rhizome (Kaempferia rotunda L.), Agar Difussion